Wheels within wheels. - Arena Wati. (Institut Terjemahan & Buku Malaysia, 2010)
Wheels within Wheels formerly entitled Tumbangnya Pokok Tak Berlangit (Fall of a Man without Principles) won the award for literary merit in the novel-writing competition sponsored by Dewan Bahasa dan Pustaka in 1962.